Seasonally sympatric but allochronic: differential expression of hypothalamic genes in a songbird during gonadal development - Bauer, Carolyn M. (Proc Biol Sci, 2018)
Allochrony, the mismatch of reproductive schedules, is one mechanism that can mediate sympatric speciation and diversification. In songbirds, the transition into breeding condition and gonadal growth is regulated by the hypothalamic–pituitary–gonadal (HPG) axis at multiple levels. We investigated whether the difference in reproductive timing between two seasonally sympatric subspecies of dark-eyed juncos (Junco hyemalis) was related to gene expression along the HPG axis. During the sympatric pre-breeding stage, we measured hypothalamic and testicular mRNA expression of candidate genes via qPCR in captive male juncos. For hypothalamic mRNA, we found our earlier breeding subspecies had increased expression of gonadotropin-releasing hormone (GnRH) and decreased expression of androgen receptor, oestrogen receptor alpha and mineralocorticoid receptor (MR). Subspecies did not differ in expression of hypothalamic gonadotropin-inhibitory hormone (GnIH) and glucocorticoid receptor (GR). While our earlier breeding subspecies had higher mRNA expression of testicular GR, subspecies did not differ in testicular luteinizing hormone receptor, follicle-stimulating hormone receptor or MR mRNA expression levels. Our findings indicate increased GnRH production and decreased hypothalamic sensitivity to sex steroid negative feedback as factors promoting differences in the timing of gonadal recrudescence between recently diverged populations. Differential gene expression along the HPG axis may facilitate species diversification under seasonal sympatry.